2016
DOI: 10.1051/matecconf/20164702001
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistance of Recycled Aggregate Concrete with Single and Hybrid Fibers

Abstract: Abstract. This paper presents a recycled aggregate concrete (RAC) mix that has been modified by adding treated recycled concrete aggregate (RCA) and various types of fiber-reinforced systems. The effectiveness of these modifications in terms of energy absorption and impact resistance was evaluated and compared with that of the corresponding regular concrete, as well as with unmodified RAC specimens. Results clearly indicate that although modification of the RAC mix with treated RCA significantly enhances the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, there is still ongoing controversy regarding the efficiency of using recycled rubber granules in concrete production, particularly with regards to the associated drop in mechanical strength [28]. Although various studies explored TSC in terms of its performance under static loading [27,29], there is a dearth of information on its performance under impact loads.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still ongoing controversy regarding the efficiency of using recycled rubber granules in concrete production, particularly with regards to the associated drop in mechanical strength [28]. Although various studies explored TSC in terms of its performance under static loading [27,29], there is a dearth of information on its performance under impact loads.…”
Section: Introductionmentioning
confidence: 99%
“…When nanosilica was put into the mixture, the impact energy for mixtures with and without steel fibers can be further enhanced by 1.3–3.5 times [ 101 ]. The enhancement was attributed to the improvement in microstructure, especially reduced porosity and modified interfacial transition zone, which affect fracture propagation directly [ 108 ].…”
Section: Other Propertiesmentioning
confidence: 99%
“…They concluded that the specimen with fiber content of 1% combined with 25% PP and 75% NY fiber presents better performance in terms of the compressive strength, flexural strength, and split tensile strength of concrete compared with other specimens. In another research, Ismail and Ramli [21] observed that a recycled aggregate concrete mix incorporated with hybrid fibers (polyolefin and PP fibers) exhibits higher impact resistance characteristics than single fiber specimens. Although present studies have analyzed the utilization of hybrid fibers in reinforced recycled aggregate concrete composites, the benefits of hybrid fibers in enhancing the various properties of mortar using FRA remain unclear.…”
Section: Introductionmentioning
confidence: 97%